Reversible tuning of luminescence and magnetism in a structurally flexible erbium-anilato MOF - Monni, Noemi; Baldoví, Jos J; García-López, Víctor; Oggianu, Mariangela; Cadoni, Enzo; Quochi, Francesco; Clemente-León, Miguel; Mercuri, Maria Laura; Coronado, Eugenio (Chemical science (Cambridge), 2022)
By combining 3,6- N -ditriazolyl-2,5-dihydroxy-1,4-benzoquinone (H 2 trz 2 An) with NIR-emitting Er III ions, two different 3D neutral polymorphic frameworks ( 1a and 1b ), differing in the number of uncoordinated water molecules, formulated as [Er 2 (trz 2 An) 3 (H 2 O) 4 ] n · x H 2 O ( x = 10, a ; x = 7, b ), have been obtained. The structure of 1a shows layers with (6,3) topology forming six-membered rings with distorted hexagonal cavities along the bc plane. These 2D layers are interconnected through the N4 atoms of the two pendant arms of the trz 2 An linkers, leading to a 3D framework, where neighboring layers are eclipsed along the a axis, with hexagonal channels filled with water molecules. In 1b , layers with (6,3) topology in the [101] plane are present, each Er III ion being connected to three other Er III ions through bis-bidentate trz 2 An linkers, forming rectangular six-membered cavities. 1a and 1b are multifunctional materials showing coexistence of NIR emission and field-induced slow relaxation of the magnetization. Remarkably, 1a is a flexible MOF, showing a reversible structural phase transition involving shrinkage/expansion from a distorted hexagonal 2D framework to a distorted 3,6-brickwall rectangular 3D structure in [Er 2 (trz 2 An) 3 (H 2 O) 2 ] n ·2H 2 O ( 1a_des ). This transition is triggered by a dehydration/hydration process under mild conditions (vacuum/heating to 360 K). The partially dehydrated compound shows a sizeable change in the emission properties and an improvement of the magnetic blocking temperature with respect to the hydrated compound, mainly related to the loss of one water coordination molecule. Theoretical calculations support the experimental findings, indicating that the slight improvement observed in the magnetic properties has its origin in the change of the ligand field around the Er III ion due to the loss of a water molecule. Tuning of luminescent and SIM properties is herein reported, in a novel flexible 3D anilato-based Er III -MOF, displaying reversible shrinkage/expansion from a distorted hexagonal to a 3,6-brickwall rectangular structure.